1985
DOI: 10.1007/bf03186274
|View full text |Cite
|
Sign up to set email alerts
|

Application of sex pheromones in sugarcane pest management

Abstract: Seven species of moth borers are known to cause heavy losses in sugarcane production in different parts of the country. Because of their concealed habits, the control of these borers becomes complex and hence a number of methods have been tried to suppress their field population. The sell behaviour of four species of these borers viz., internode borer, stalk borer, shoot borer and top borer have been studied in recent years and among these the internode borer and stalk borer have been found to have potent sex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…Gas chromatographic analyses of ovipositor washings from female C. sacchariphagus indicus showed Z13-18:Ac and Z13-18:Alc as the main components Field tests in India demonstrated that blends of the two components were attractive to male moths in similar ratios as for C. sacchariphagus in Mauritius (David et al, 1985). sacchariphagus indicus.…”
Section: Pheromone Identificationmentioning
confidence: 92%
See 1 more Smart Citation
“…Gas chromatographic analyses of ovipositor washings from female C. sacchariphagus indicus showed Z13-18:Ac and Z13-18:Alc as the main components Field tests in India demonstrated that blends of the two components were attractive to male moths in similar ratios as for C. sacchariphagus in Mauritius (David et al, 1985). sacchariphagus indicus.…”
Section: Pheromone Identificationmentioning
confidence: 92%
“…During the period -1985, Tanaka et al (1987 demonstrated effective control of the second flight of adult C. suppressalis using either Zll-16:Ald alone or Z9-16:Ald,Zll-16:Ald and Z13-18:Ald combined. These were dispensed from the Shinetsu twist-ties at 12.5 mg/ha/day for low populations and 25 mg/ha/day for high populations, over areas of greater than 20 ha.…”
Section: Mating Disruption Ofc Suppressalismentioning
confidence: 99%
“…These include the sugarcane stalk borer, Chilo auricilius (David et al, 1985) and C. infuscatellus Snell; lady's finger fruit and shoot borers, Earias insulana Boisd. and E. vittella Fab.…”
Section: Role Of Pheromonesmentioning
confidence: 99%
“…The female moths of C. auricilius produce a sex pheromone which has been identified as a mixture of (Z)-7dodecenyl acetate, (Z)-8-tridecenyl acetate, (Z)-9-tetradecenyl acetate and (Z)-lO-pentadecenyl acetate (David et al, 1985). The female moths of C. auricilius produce a sex pheromone which has been identified as a mixture of (Z)-7dodecenyl acetate, (Z)-8-tridecenyl acetate, (Z)-9-tetradecenyl acetate and (Z)-lO-pentadecenyl acetate (David et al, 1985).…”
Section: Chilo Auricilius Dudgeonmentioning
confidence: 99%